SUNAFIL’s labor rights education campaigns on TikTok - Fonseca, Massiel Alejandra Alarcón (2024)
The goal of the research is to identify how the educational campaigns on labor rights carried out by SUNAFIL through the social network TikTok are perceived. The study has a qualitative approach, through interviews with young workers between 20 and 25 years of age in Metropolitan Lima, users of the TikTok platform. As a result, a lack of advertising resources in the institution for the dissemination of labor rights was evidenced. However, the use of TikTok as media, as it is a social network, makes it possible to generate proximity by providing the public with educational information at their fingertips. In this way, SUNAFIL’s communication is perceived as positive and close, even more when public institutions keep a distant and formal profile, perceived as disinterested in the needs of the population. It is recommended in the communication strategy to use this digital channel to communicate the work of public entities.